Analysis of Student Satisfaction with School Administration Services - Santosa, Achadi Budi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study investigated students’ satisfaction with administrative services at the Senior High School level in the Yogyakarta area. Using a quantitative descriptive approach, data were collected through a Likert-scale questionnaire distributed to 104 students and analyzed using descriptive statistics. The findings of the study indicated that the overall level of student satisfaction was categorized as “good,” with a mean score of 3.4 and a dominant median value of 4 across 12 service indicators. Key service aspects, such as comfort of service space, adequacy of facilities, responsiveness, clarity of communication, empathy, and non-discrimination, received good ratings, although some indicators, particularly those related to complaint handling and physical comfort, needed improvement. This study highlights the importance of continuous improvement in service quality to meet students’ expectations and strengthen the reputation of the institution. Future research is encouraged to adopt a longitudinal design to assess the sustainability of service improvements and explore the determinants of satisfaction in varying educational contexts.